2022
DOI: 10.1101/2022.07.27.501794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A developmental atlas of the mouse brain by single-cell mass cytometry

Abstract: Development of the mammalian brain requires precisely controlled differentiation of neurons, glia, and nonneural cells. To investigate protein-level changes in these diverse cell types and their progenitors, we performed single-cell mass cytometry on whole brain (E11.5/E12.5) and microdissected telencephalon, diencephalon, mesencephalon, and rhombencephalon (E13.5-P4) collected at daily timepoints from C57/BL6 mice. Measuring 24,290,787 cells from 112 sample replicates with a 40-antibody panel, we quantified 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…The four GBM cell types described by Neftel et al are delineated by gene expression [19]. Recent studies have shown that such transcriptional cell-type markers often do not translate to protein level markers for use in approaches such as IMC[13, 32]. We set out to test this for the GBM neoplastic cell types, specifically.…”
Section: Resultsmentioning
confidence: 99%
“…The four GBM cell types described by Neftel et al are delineated by gene expression [19]. Recent studies have shown that such transcriptional cell-type markers often do not translate to protein level markers for use in approaches such as IMC[13, 32]. We set out to test this for the GBM neoplastic cell types, specifically.…”
Section: Resultsmentioning
confidence: 99%
“…Imaging mass cytometry (IMC) with IMS is another approach that can be used to study cell types, subcellular compartments, and cell-type-specific synapses [2]. IMC uses antibodies coupled to heavy metal species to label proteins, allowing the simultaneous imaging of up to 40 different proteins, with labeled proteins identified by IMS [135,136]. In Van Deusen et al, protein-based cell atlases of the developing mouse telencephalon, diencephalon, mesencephalon, and rhombencephalon were mapped using this approach.…”
Section: Direct In Situ Spatial Proteomicsmentioning
confidence: 99%
“…In Van Deusen et al, protein-based cell atlases of the developing mouse telencephalon, diencephalon, mesencephalon, and rhombencephalon were mapped using this approach. They quantified 85 molecularly distinct cell populations, including neurons and myelin [136].…”
Section: Direct In Situ Spatial Proteomicsmentioning
confidence: 99%